PROBLEMS AND SOLUTIONS IN TEACHING FOREIGN LANGUAGE TO STUDENTS OF HIGHER EDUCATION - Rahmonova, Saodat (Журнал иностранных языков и лингвистики, 2023)
One of the goals is to ensure the quality of education of the currently growing younger generation in foreign languages, radically improve the education system of professionals who can freely speak foreign languages, train mature personnel that meets world educational standards, through mastery of foreign languages ​​of the educational reform carried out in our country. This article focuses on the difficulties of learning a foreign language as a second language and suggestions for solving these problems.